2001
DOI: 10.1063/1.1335620
|View full text |Cite
|
Sign up to set email alerts
|

Spatial profiles of neutral, ion, and etch uniformity in a large-area high-density plasma reactor

Abstract: Spatial profiles of neutral density, ion density, and etch rate have been measured in a large-area high-density plasma reactor. Blanket photoresist films on 200 mm wafers are etched by oxygen plasmas in a magnetized inductively coupled plasma reactor. Ion density and relative neutral density are measured by a scanning Langmuir probe and optical probe, respectively. Spatially resolved atomic oxygen density is then measured by optical emission spectroscopy and spatially resolved actinometry. The etch rate is cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The neutral atom in an oxygen discharge has a behavior different from that in the monatomic feed gas case like argon. The calculated radial distributions of oxygen atoms are in agreement with the experimental results [1,4]. The profile of oxygen atom is parabolic (peaked in the plasma center) or hollow, depending on the gas pressure.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The neutral atom in an oxygen discharge has a behavior different from that in the monatomic feed gas case like argon. The calculated radial distributions of oxygen atoms are in agreement with the experimental results [1,4]. The profile of oxygen atom is parabolic (peaked in the plasma center) or hollow, depending on the gas pressure.…”
Section: Resultssupporting
confidence: 81%
“…Thus, the mechanisms that determine the uniformity of chemically reactive neutrals are of interest. Process uniformity depends strongly on the spatial distribution of both charged and neutral particle densities and velocities, as well as potentials [1,2]. Process uniformity is a key requirement to enable large wafers or flat panels to be processed by plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] It has been shown that there is a strong correlation between the radial variation of radical concentration and the yield of a plasma process. 8 Measurements of the relative spatial distributions of radical densities have been constructed using various optical measurement techniques, such as laser induced fluorescence, 9,10 optical emission spectroscopy ͑OES͒, and absorption spectroscopy. 11 OES, which measures the optical emission of species in the plasma, is the most popular semiconductor plasma process diagnostic technique because of its simplicity, high sensitivity, and wide applicability.…”
Section: Introductionmentioning
confidence: 99%
“…3,[11][12][13] Otherwise, a movable electro-optical probe is inserted into the plasma to directly detect spatial variations in species concentration by collecting the emission of the molecules in front of the probe. 8,14,15 In the present work, we designed an OES that is capable of detecting spatial variations in plasma density, and we constructed this OES with a series of lenses, apertures, and a pinhole as a spatial filter to enhance the spatial resolution. We theoretically verified the spatial resolution capability of the OES, and the results of the calculation were compared with experiments.…”
Section: Introductionmentioning
confidence: 99%